Heart–Brain Axis: Effects of Neurologic Injury on Cardiovascular Function. Issue 3 (3rd February 2017) - Tahsili-Fahadan, Pouya; Geocadin, Romergryko G.
Abstract : A complex interaction exists between the nervous and cardiovascular systems. A large network of cortical and subcortical brain regions control cardiovascular function via the sympathetic and parasympathetic outflow. A dysfunction in one system may lead to changes in the function of the other. The effects of cardiovascular disease on the nervous system have been widely studied; however, our understanding of the effects of neurological disorders on the cardiovascular system has only expanded in the past 2 decades. Various pathologies of the nervous system can lead to a wide range of alterations in function and structure of the cardiovascular system ranging from transient and benign electrographic changes to myocardial injury, cardiomyopathy, and even cardiac death. In this article, we first review the anatomy and physiology of the central and autonomic nervous systems in regard to control of the cardiovascular function. The effects of neurological injury on cardiac function and structure will be summarized, and finally, we review neurological disorders commonly associated with cardiovascular manifestations.